STUDENTS THINKING PROCESS IN SOLVING THE PROBLEMS OF SOCIAL ARITHMETIC STORIES TEST BASED ON GENDER - Nurhayati, Ai Siti; Aripin, Usman (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
Abstract: This study aims to find out how the thinking process of female and male students in solving problems analyzed using thinking type indicators according to Zuhri and Wing that divided into three, namely conceptual, semi-conceptual, and computational thinking processes. This research method used a qualitative descriptive study. The instrument in the study consisted of test questions given to 34 VII grade students in one of Junior High School in Cimahi. Based on the results, can be known about the conceptual thinking process only done by female students with a percentage of 11.8%, the semi-conceptual thinking process of female students was 64.7% and 47% of male students, as for computational thinking process of female students was 23.5% and 53% male students. From the results of this study, it can be concluded that female students tend to think semi-conceptually while male students tend to think computationally. Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana proses berpikir siswa perempuan dan laki-laki dalam menyelesaikan masalah yang dianalisis menggunakan indikator jenis berpikir menurut Zuhri dan Wing yang dibagi menjadi tiga yaitu proses berpikir konseptual, semi-konseptual, dan komputasi. Metode penelitian ini berupa penelitian deskriptif kualitatif. Instrumen dalam penelitian berupa soal tes yang diberikan kepada 34 siswa kelas VII SMP di Kota Cimahi. Berdasarkan hasil penelitian yang telah dilakukan dapat diketahui bahwa proses berpikir konseptual hanya dilakukan siswa perempuan dengan persentase 11,8%, proses berpikir semi-konseptual siswa perempuan adalah 64,7% dan siswa laki-laki 47%, sedangkan untuk proses berpikir komputasi siswa perempuan adalah 23,5% dan siswa laki-laki 53%. Dari hasil penelitian tersebut dapat disimpulkan bahwa siswa perempuan cenderung berpikir secara semikonseptual, sedangkan siswa laki-laki cenderung berpikir secara komputasional.